RETRACTION Polevoy, G. (2024). El efecto de la carrera aeróbica en el pensamiento y la resistencia de los niños (The effect of aerobic running on children’s thinking and endurance). Retos, 54, 303–311. https://doi.org/10.47197/retos.v54.103477 - RETOS, RETOS (Retos, 2025)
Polevoy, G. (2024). El efecto de la carrera aeróbica en el pensamiento y la resistencia de los niños (The effect of aerobic running on children’s thinking and endurance). Retos, 54, 303–311. https://doi.org/10.47197/retos.v54.103477 Retraction of the article by the editor of the journal. Due to plagiarism by the author.